Gender, marginalised groups, and young people's mental health: a longitudinal analysis of trajectories - Lereya, ST; Norton, S; Crease, M; Deighton, J; Labno, A; Ravaccia, GG; Bhui, K; Brooks, H; English, C; Fonagy, P; Heslin, M; Edbrooke-Childs, J (BioMed Central, 2024)
Background: Individuals from marginalised groups experience higher levels of mental health difficulties and lower levels of wellbeing which may be due to the exposure to stress and adversity. This study explores trajectories of mental health over time for young women and girls and young people with other marginalised identities. Methods: We conducted a secondary analysis on N = 14,215 children and young people (7,501 or 52.8% female, 6,571 or 46.2% male, and 81 or 0.6% non-binary or questioning) who completed a survey at age 11 to 12 years and at least one other annual survey aged 12 to 13 years and/or aged 13 to 14 years. We used group-based trajectory models to examine mental health difficulties. Results: Except for behavioural difficulties, young women’s and girls’ trajectories showed that they consistently had higher levels of mental health difficulties compared to young men and boys. A similar pattern was shown for non-binary and questioning children and young people. Children and young people with economic disadvantage and/or special education needs, and/or for whom there were welfare concerns, were generally more likely to experience higher levels of mental health difficulties. Conclusions: This information could inform public policy, guidance and interventions.